Neutrophil-Lymphocyte Ratio and LDH/Albumin Ratio as Biomarkers for Severity and Mortality in Acute Pancreatitis - Bengi, Göksel; Çelik, İbrahim; Dolu, Süleyman; Önem, Soner; Soytürk, Müjde; Rendeci, Serkan; Topalak, Ömer; Akpinar, Hale (Turkish Journal of Gastroenterology, 2025)
Background/Aims: Acute pancreatitis (AP) is a common and potentially severe condition, and early identification of its severity is critical for appropriate clinical management. This study aimed to investigate the role of the Neutrophil-Lymphocyte Ratio (NLR) and Lactate dehydrogenase (LDH)/Albumin Ratio (LAR) in predicting the severity and prognosis of patients with AP and to determine the optimal NLR value. Materials and Methods: The demographic, clinical, and laboratory data of patients diagnosed with AP were retrospectively analyzed. Neutrophil-Lymphocyte Ratio was measured at admission (0 hours), and at 24 and 48 hours; C-reactive protein (CRP) values were recorded at 0 and 48 hours; and the LAR was calculated based on LDH and albumin values measured at 48 hours post admission. These values were compared with disease severity, mortality, organ failure, length of hospital stay, and the need for intensive care according to Ranson and bedside index of severity in AP (BISAP) scores. Results: According to the BISAP scoring, 38 patients (16%) were classified as having severe AP, while 200 patients (84%) had mild AP. The best parameter for predicting severe AP was found to be the 24-hour NLR with a sensitivity of 79% and specificity of 67%. The best parameter for predicting mortality and organ failure was the NLR at 48 hours. There was a statistically significant difference between the length of hospital stay and the need for intensive care with the CRP value at 48 hours. Additionally, there was a statistically signifi cant relationship between LAR and mortality, length of hospital stay, organ failure, and the need for intensive care. Conclusion: This study demonstrates that the NLR and the LDH/Albumin Ratio are important and easily accessible markers for deter mining the severity and prognosis of AP. The NLR at 48 hours is an effective parameter for predicting mortality and organ failure, while the LDH/Albumin Ratio is significant in predicting mortality. Cite this article as: Bengi G, Çelik İ, Dolu S, et al. Neutrophil-lymphocyte ratio and LDH/albumin ratio as biomarkers for severity and mortality in acute pancreatitis. Turk J Gastroenterol. 2025;36(8):497-507.